Can you breathe yourself to a better pelvic floor? A systematic review - Bø, Kari; Driusso, Patricia; Jorge, Cristine Homsi (Universidade Federal de São Carlos, 2023)
The primary aim of the present study was to investigate the evidence for breathing as an intervention alone or in addition to PFM contraction in treatment of UI and POP. Materials & Methods This systematic review included short-term experimental studies and randomize controlled trials (RCTs) indexed on PubMed, EMBASE, and PEDro database. A form was used to extract data that was analyzed qualitatively due to the heterogeneity in interventions and outcome measures of the included studies. The individual methodological quality of RCTs was analyzed using the PEDro scale. Results A total of 18 studies were included, 374 participants from short-term experimental studies and 765 from nine RCTs. PEDro score varied from 4 to 8. Activation of the PFM during expiration was significantly less than during a PFM contraction. In general, the RCTs showed that training the PFM is significantly more effective to improve PFM variables and UI and POP than breathing exercises, and that adding breathing exercises to PFMT have no additional effect. Conclusion This systematic review indicates that the evidence for incorporating breathing exercise in clinical practice in addition to or instead of PFMT is scant or non-existing, both based on short-term experimental studies and small RCTs.
Keywords: Breathing; Pelvic floor; Physiotherapy; Women's health; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL